Evaluasi Penggunaan Antibiotik dengan Metode Kuantitatif pada Pasien Pneumonia Rawat Inap di Rumah Sakit Nusa Tenggara Barat - Khairani, Sondang; Ramadaniati, Hesty Utami; Sarnianto, Prih; Kristin, Erna; Anggriani, Yusi (Faculty of Pharmacy, Universitas Pancasila, 2023)
Abstract Overuse of antibiotics is a public health challenge that can lead to antimicrobial resistance. To reduce the occurrence of antibiotic resistance, it is necessary to evaluate the use of antibiotics to determine the rational use of drugs using quantitative methods, namely the ATC /DD method. The purpose of the study was to determine the use of antibiotics and describe the pattern of antibiotic use in inpatients at West Nusa Tenggara Hospital using the ATC /DD method and DU90%. The research method is a cross-sectional study design with retrospective data collection on adult pneumonia patients hospitalized in the period Januari-December 2019 and 2022, data obtained from medical records. The results of the study met the inclusion criteria of 218 patients with the majority being male 117 (53.67%) and the most age > 65, namely 66 (30.28%). Antibiotic use has a total DDD value of 185.56 DDD/100 days of care with the highest antibiotic DDD value being ceftriaxone which is 104.00 DDD/100 days of hospitalization while antibiotics that are included in the DU 90% are ceftriaxone, levofloxacin, cefoperazon and meropenem. Conclusion the most antibiotics used were ceftriaxone 104.00 DDD/100 days of length of stay.